DEVELOPMENT OF EXACT SCIENCES IN UZBEKISTAN DURING THE SECOND WORLD WAR (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
The Second World War created many difficulties in the Uzbek SSR as well as in the entire USSR. First of all, it should be emphasized that the country's economy and science are under great pressure. The transfer of enterprises, factories and research institutions from the western and central regions, where the risk of war is high, to the eastern and southern regions, which are considered relatively safe, helped to save the life of the above-mentioned industries.As in all areas, representatives of the scientifi